A prospective study on enterocutaneous fistula in a tertiary care centre: A single institution study - Karthikeyan Selvaraj; Rajalakshmi Ramamurthy; Prithvinathan V; Sasikumar Patabi (Creative Pharma Assent, 2023)
Background: Aberrant connection linking gastrointestinal tract and the skin is termed Enterocutaneous fistula. Enterocutaneous fistulas can lead to significant morbidity and mortality. Death pertaining to enterocutaneous fistulas remains enormous when juxtaposed with other surgeries. The treatment of Enterocutaneous fistula may be a significant challenge to surgeons and gastroenterologists.Â Method: After obtaining ethical committee clearance, a total of 25 patients of Enterocutaneous fistula who presented to Surgical department and Surgical Gastroenterology department were included in the study. The cause, site and output of fistula, clinical course and complications of fistula were studied. Patients were managed either surgically or conservatively depending on the output of the fistula, nutrition and metabolic profile. Results: 19 patients were managed conservatively and 6 patients were managed surgically. Amidst the conservative group, 16 out of 19 patients had spontaneous closure of fistula and remaining three had died as fistulas failed to close. Surgical closure was accomplished in 5 patients but failed in one patient and that patient died. 96% (24 out of 25) of patients in our study had developed fistula post operatively. Among 25 patients studied, nearly 44% each i.e., 11 out of 25 patients had colonic and small bowel fistula respectively followed by fistula at appendix accounting for 12% (i.e., Fistula Output: 11 (44%) fistulae were low output, 8 (32%) were medium output. Conclusion: Enterocutaneous fistulas are more common in postoperative period. Conservative treatment should be the mainstay in management of Enterocutaneous fistula.